Forgiveness as singularity: The "Allah" controversy in Malaysia and the church's public discourse of cheek‐turning. Issue 1 (6th March 2018) - Lau, Alwyn
Abstract: This paper adopts a Lacanian motif to present the world as being psycho‐theologically characterized by sacrifice and loss, with its subjects (including, more often than not, Christians) remaining in bondage to a vicious cycle of tit‐for‐tat violence and retribution. The chief solution to this situation is for the church to mimic the mercy, forgiveness, and cheek‐turning displayed by Jesus. Through via unconditional forgiveness in the face of injustice and oppression, the community defined by the enemy‐loving work of Christ can exemplify an unravelling of the present diabolical world system. In Lacanian terms, the church is responsible to initiate an ongoing assault of the Real (of peace‐making and forgiveness) upon the Symbolic Order (of rights‐seeking and oppression). This article argues that turning the cheek is no mere political tactic, but is indeed the church's singularity, that is, that aspect of a subject whose  jouissance  (or enjoyment) refuses the validation of the Other. It concludes by highlighting two episodes from the "Allah" controversy in Malaysia where Christian leaders prioritized forgiveness and reconciliation over legal reprisal.